2000
DOI: 10.1128/jb.182.23.6854-6856.2000
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Peptidoglycan Biosynthesis in Mycobacteria: Characterization of a ddlA Mutant of Mycobacterium smegmatis

Abstract: A temperature-sensitive mutant of Mycobacterium smegmatis was characterized that contains a mutation in ddlA, the gene encoding D-alanine:D-alanine ligase. Enzymatic assays using recombinant proteins and Dcycloserine susceptibility indicate that the A365V mutation in the SMEG35 DdlA protein causes a reduction in enzymatic activity in vitro and in vivo.A nearly universal component of bacterial cell walls is peptidoglycan, a macromolecule that is composed of polysaccharide chains that are cross-linked by short p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…We reasoned that a more precise gauge for MurF-dependent incorporation of the intact probe would be whether it could support the replication of a strain unable to ligate d -alanine to itself. Therefore, we confirmed that alkDADA rescues the growth of a temperature-sensitive ddlA mutant (47) at the non-permissive temperature ( Figure 4B ).…”
Section: Resultssupporting
confidence: 73%
“…We reasoned that a more precise gauge for MurF-dependent incorporation of the intact probe would be whether it could support the replication of a strain unable to ligate d -alanine to itself. Therefore, we confirmed that alkDADA rescues the growth of a temperature-sensitive ddlA mutant (47) at the non-permissive temperature ( Figure 4B ).…”
Section: Resultssupporting
confidence: 73%
“…In this context, D-alanine ligase is an attractive candidate since this enzyme activity is also inhibited by DCS (13). More importantly, the construction of a conditionally lethal mutant bank led to the isolation of a thermosensitive mutant impaired in this gene function (3). Furthermore, DCS hypersusceptibility may reflect an alteration of the peptidoglycan structure of TAM23 cells, as a direct consequence of the inactivation of the alr gene.…”
Section: Discussionmentioning
confidence: 99%
“…BNC1 (66%), Zymomonas mobilis (62%), S. meliloti (62%), and Bartonella bacilliformis (61%) among others. D-Alanine-D-alanine ligase is an enzyme involved in peptidoglycan biosynthesis (Belanger et al, 2000). Immediately downstream of ddlB and transcribed in the same direction, three complete ORFs could be identified.…”
Section: Genetic Characterization Of the Tn5-interrupted Region Presementioning
confidence: 99%